Meaning Shift in Arabic Social Media: A Cultural-Semantic Study - Harianto, Neldi; Afria, Rengki; Izar, Julisah; Defrianti, Denny; Hasani, Salman (Institut Agama Islam Negeri Curup, 2025)
The phenomenon of social media has introduced new dynamics in the development of the Arabic language, particularly in relation to shifts in vocabulary meanings influenced by cross-cultural interaction, digital technology, and online communication practices. This study aimed to examine meaning shifts in Arabic as used on social media through a cultural-semantic approach. The research focused on identifying vocabulary items that underwent semantic change, whether through narrowing, broadening, or connotative shifts, and on analyzing the cultural factors underlying these changes. The study employed a qualitative method using a cultural-semantic framework, with data drawn from utterances, posts, and conversations circulating on popular platforms such as Twitter (X), Instagram, and TikTok. The findings indicate that semantic shifts in Arabic social media emerge through complex interactions among linguistic, social, and cultural dimensions. Based on Cruse’s theory of semantics, most meaning changes occur at the level of sense relations, primarily through mechanisms such as broadening, narrowing, and metaphorical extension. For instance, the word متابع (mutābi‘), which lexically means “follower,” has undergone narrowing to specifically denote a “social media follower” in the digital context. From Duranti’s perspective of cultural semantics, these shifts are not merely linguistic phenomena but also reflect processes of identity formation and value negotiation within Arab digital communication culture. Each term that experienced semantic change embodies the dynamics of digital life, reflecting values such as ijtima‘iyyah (social connectedness), shuhrah (popularity), and ta‘bīr dhāti (self-expression).